2002
DOI: 10.1093/clinchem/48.12.2131
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of Essential Hypertension Single-Nucleotide Polymorphisms by a Homogeneous PCR Method with Universal Energy Transfer Primers

Abstract: Background: Human hypertension is a complex, multifactorial disease with a heritability of more than 30–50%. A genetic screening test based on analysis of multiple single-nucleotide polymorphisms (SNPs) to assess the likelihood of developing hypertension would be helpful for disease management. Methods: Tailed allele-specific primers were designed to amplify by PCR six biallelic SNP loci [three in G protein-coupled receptor kinase type 4 (GRK4): R65L, A142V, and A486V; two in angiotensinogen: −6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(40 citation statements)
references
References 46 publications
2
37
1
Order By: Relevance
“…Although we have found that the A486V polymorphism is associated with HT in the northern Chinese Han population, this result contradicts those found in studies of Caucasian Italians (Bengra et al 2002) and Caucasian Australians (Speirs et al 2004). In their studies the V486 allele was found to be the risk factor for HT, while in ours A486 was shown to be associated with HT.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although we have found that the A486V polymorphism is associated with HT in the northern Chinese Han population, this result contradicts those found in studies of Caucasian Italians (Bengra et al 2002) and Caucasian Australians (Speirs et al 2004). In their studies the V486 allele was found to be the risk factor for HT, while in ours A486 was shown to be associated with HT.…”
Section: Discussioncontrasting
confidence: 99%
“…Three variants of the γ isoform of GRK4 , R65L , A142V and A486V have been reported to affect GRK activity, resulting in increased serine phosphorylation of D 1 receptors and uncoupling of the receptor from its G‐protein complex. Bengra et al (2002) deserved a significant association ( P = 0.034) between V486 and an Italian population of mildly hypertensive patients. In another study the V486 allele was also found to be associated with HT ( P = 0.02), and additionally the L65 and the V142 alleles tracked with elevation in diastolic blood pressure (DBP), even though this was seen only in male HTs ( P = 0.009; P = 0.002, respectively) (Speirs et al 2004).…”
Section: Introductionmentioning
confidence: 94%
“…More recently GRK4 variants have been associated with a decreased response to beta-blocker treatment for HBP in African American males. 28 32 A metaanalysis of the major studies involving GRK4 variants and HBP showed that the allele 486V increases the risk for HBP with an OR of 1.5 (95% CI: 1.2-1.9). 33 Other studies have found associations between the A142V variant 34 and HBP in a Japanese population.…”
Section: Discussionmentioning
confidence: 99%
“…The GRK4 locus on human chromosome 4p16.3 is linked to essential hypertension and salt sensitivity. [79][80][81][82][83][84][85] Three missense SNPs ( ie, 65R>L, 142A>V, and 486A>V) in the coding region of GRK4c are associated with increased blood pressure. Depending on the genetic background of the mouse, mice overexpressing the GRK4c wild-type transgene are normotensive and salt-resistant, whereas GRK4c142V transgenic mice have high blood pressure even with normal NaCl intake.…”
Section: G Protein-coupled Receptor Kinasementioning
confidence: 99%
“…The association between GRK4486V and essential hypertension was found in Italian and Euro-Australian populations. 79,80 In a study of northern Han Chinese participants, the GRK465L, GRK4142V, and GRK4A486 haplotypes are associated with a 6-fold higher risk of systolic and diastolic hypertension. 81 In these same Han Chinese participants, GRK4486V alone is associated with hypertension.…”
Section: G Protein-coupled Receptor Kinasementioning
confidence: 99%